Rapid and sustained environmental responses to global warming: the Paleocene–Eocene Thermal Maximum in the eastern North Sea - E. W. Stokke; M. T. Jones; L. Riber; H. Haflidason; H. Haflidason; I. Midtkandal; B. P. Schultz; H. H. Svensen (Climate of the Past, 2021)
The Paleocene–Eocene Thermal Maximum (PETM; ∼ 55.9 Ma) was a period of rapid and sustained global warming associated with significant carbon emissions. It coincided with the North Atlantic opening and emplacement of the North Atlantic Igneous Province (NAIP), suggesting a possible causal relationship. Only a very limited number of PETM studies exist from the North Sea, despite its ideal position for tracking the impact of both changing climate and NAIP activity. Here we present sedimentological, mineralogical, and geochemical proxy data from Denmark in the eastern North Sea, exploring the environmental response to the PETM. An increase in the chemical index of alteration and a kaolinite content up to 50 % of the clay fraction indicate an influx of terrestrial input shortly after the PETM onset and during the recovery, likely due to an intensified hydrological cycle. The volcanically derived zeolite and smectite minerals comprise up to 36 % and 90 % of the bulk and clay mineralogy respectively, highlighting the NAIP's importance as a sediment source for the North Sea and in increasing the rate of silicate weathering during the PETM. X-Ray fluorescence element core scans also reveal possible hitherto unknown NAIP ash deposition both prior to and during the PETM. Geochemical proxies show that an anoxic to sulfidic environment persisted during the PETM, particularly in the upper half of the PETM body with high concentrations of molybdenum (MoEF > 30), uranium (UEF up to 5), sulfur (∼ 4 wt %), and pyrite (∼ 7 % of bulk). At the same time, export productivity and organic-matter burial reached its maximum intensity. These new records reveal that negative feedback mechanisms including silicate weathering and organic carbon sequestration rapidly began to counteract the carbon cycle perturbations and temperature increase and remained active throughout the PETM. This study highlights the importance of shelf sections in tracking the environmental response to the PETM climatic changes and as carbon sinks driving the PETM recovery.